The growth-employment-poverty nexus in Latin America in the 2000s: Dominican Republic Country Study - Cruces, Guillermo Antonio (2015)
During the 2000s, the Dominican Republic experienced above-average economic growth along with mixed results in labour market indicators. GDP per capita stagnated through 2004 and, for the most part, grew rapidly from 2005 through 2012. Comparing 2000 with 2012, many unfavourable developments were seen. Among them: an increase in unemployment; worsening in the employment composition by occupation and position; a substantial fall in labour earnings; and no progress in reducing poverty. The international crisis slowed economic growth but did not reverse it and had a negative effect on some labour indicators, which failed to return to pre-crisis levels by 2012.